2021
DOI: 10.21203/rs.3.rs-600041/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Deforestation Impacts on Amazon-Andes Hydroclimatic Connectivity

Abstract: Amazonian deforestation has accelerated during the last decade, threatening an ecosystem where almost one third of the regional rainfall is transpired by the local rainforest. Due to the precipitation recycling, the southwestern Amazon, including the Amazon-Andes transition region, is particularly sensitive to forest loss. This study evaluates the impacts of Amazonian deforestation in the hydro-climatic connectivity between the Amazon and the eastern tropical Andes during the austral summer (December-January-F… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 165 publications
(198 reference statements)
0
9
0
2
Order By: Relevance
“…During the recent decades, STSA has experienced an increase in dry conditions over southern Amazonia – around 5°–15°S and 70°–50°W – during the dry‐to‐wet transition season (approximately from July to October) and a lengthening of the dry season associated with a delayed SAMS onset (Arias et al., 2015; Correa et al., 2021; Debortoli et al., 2015; Espinoza et al., 2019; Fu et al., 2013; Giráldez et al., 2020; Pascale et al., 2019). The most recent climate report of the Intergovernmental Panel on Climate Change (IPCC) indicates high confidence on a delayed onset of the SAMS, which is influenced by anthropogenic forcings such as land‐use and deforestation changes, that induce modifications in the STSA hydrological cycle and atmospheric circulation (Alves et al., 2017; Caballero et al., 2022; Costa & Pires, 2010; Marengo et al., 2018; Ruiz‐Vasquez et al., 2020; Sierra et al., 2021; Silva et al., 2020; Wongchuig et al., 2021; Zilli & Carvalho, 2021). All of these topics are currently central issues within the scientific community since the modification of the surface‐atmosphere feedbacks endangers biodiversity and human activities (Bombardi et al., 2019; Gatti et al., 2021; Staal et al., 2018).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…During the recent decades, STSA has experienced an increase in dry conditions over southern Amazonia – around 5°–15°S and 70°–50°W – during the dry‐to‐wet transition season (approximately from July to October) and a lengthening of the dry season associated with a delayed SAMS onset (Arias et al., 2015; Correa et al., 2021; Debortoli et al., 2015; Espinoza et al., 2019; Fu et al., 2013; Giráldez et al., 2020; Pascale et al., 2019). The most recent climate report of the Intergovernmental Panel on Climate Change (IPCC) indicates high confidence on a delayed onset of the SAMS, which is influenced by anthropogenic forcings such as land‐use and deforestation changes, that induce modifications in the STSA hydrological cycle and atmospheric circulation (Alves et al., 2017; Caballero et al., 2022; Costa & Pires, 2010; Marengo et al., 2018; Ruiz‐Vasquez et al., 2020; Sierra et al., 2021; Silva et al., 2020; Wongchuig et al., 2021; Zilli & Carvalho, 2021). All of these topics are currently central issues within the scientific community since the modification of the surface‐atmosphere feedbacks endangers biodiversity and human activities (Bombardi et al., 2019; Gatti et al., 2021; Staal et al., 2018).…”
Section: Introductionmentioning
confidence: 99%
“…STSA hosts the Amazonia ‐ the world's largest rainforest and one of the major sources of evapotranspiration ‐ playing a critical role in the global balances of energy, water, moisture and carbon (Gatti et al., 2021; Llopart et al., 2020). The region presents unique biodiversity and geographical patterns, mainly due to the interaction of the Amazonia and the Andes mountain range, which have deep implications in the atmospheric dynamics, moisture transport and river discharge not only throughout STSA but also in remote regions of the continent (Arias, Garreaud, et al., 2021; Espinoza et al., 2020; Sierra et al., 2021).…”
Section: Introductionmentioning
confidence: 99%
“…In the Southern Amazon, convective processes are particularly active (Vera et al ., 2006); therefore, a decrease in vertical wind could indicate a decrease in convective activity and rainfall. To gain a complete understanding of what is at play when relating the evolution of forest cover with rainfall changes, local processes should therefore be accounted for, through the use of tools such as numerical models (Eiras‐Barca et al ., 2020; Ruiz‐Vásquez et al ., 2020; Sierra et al ., 2021). For instance, in a recent high‐resolution modelling work, Sierra et al .…”
Section: Discussionmentioning
confidence: 99%
“…For instance, in a recent high‐resolution modelling work, Sierra et al . (2021) found that a deforestation scenario of 45% of the Amazonian forest produce decrease in evapotranspiration and vertically integrated moisture convergence in central and southern Amazon, which also implies a reduction in the vertical velocity. These regional changes due to Amazon deforestation are associated with a rise in the atmospheric pressure at lower levels.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation